Koncepcja rozwoju gospodarczego Polski w twórczości naukowej Fryderyka Skarbka - Romanow, Zbigniew (Wydział Prawa i Administracji UAM, 1982)
Fryderyk Skarbek thanks to tis thorough studies in France and then direct relations with socio-economic life of the post-partition Poland — paves the way for the classical theory, amplifying and adapting it to our contemporary conditions. Thanks to those scientific works he suppresses influence of physiocratic doctrine in Poland and inculcates ideas of the new system — capitalism. Fryderyk Skarbek is characterized by social ideas and detecting exploitation attendant upon development of capitalism he stipulates as just as Sismondi compromise solutions for overcoming discrepancies, but he fails to realize their inevitabilities in process of capitalism development. In contradiction to reactionary views of F. List, for whom intrinsic discrepancies of capitalism have been of minor consequence in comparison with development of German national productive forces — Skarbek's, analysis of capitalistic production relations based on clear-sightedness and understanding of social problems of that system has progressive (in contemporary terms) character. Though in the end of his life he was turning to vulgar apology of capitalism, his basic scientific output proves that he is that Polish economist who left unabatdng mark in the bourgeois economic thought.
The Conception of Economic Development of Poland in Fryderyk Skarbek's Scientific Output